The Effect of Forced Cough to Minimize Pain and Discomfort at the Time of Colposcopy-Guided Cervical Biopsy. Issue 2 (April 2020) - Kuhn, Theresa; Ukazu, Adanna; Strickland, Pamela Ohman; Roche, Natalie; Taveras, Yanille; Kovalenko, Olga; Pompeo, Lisa; Einstein, Mark
Abstract : Objective: The aim of the study was to determine whether forced cough during colposcopy-guided cervical biopsy affected pain and anxiety levels. Materials and Methods: The study was conducted at the University Hospital (Newark, NJ) Ambulatory Care Center from December 2016 to June 2018 and evaluated 110 patients at the time of a colposcopy-guided cervical biopsy. Study patients were randomized to either cough or no cough group during the biopsy procedure. Pain level was assessed using a visual analog pain scale before, during, and immediately after a colposcopy-guided cervical biopsy. Study patients also completed a standardized anxiety survey before and after the procedure. T tests, Pearson χ 2, or Cochran-Mantel-Haenszel were used to compare baseline characteristics between the cough and no cough groups. Multivariate linear regression analysis was used to identify potential confounders and then compare pain levels across both groups. Results: There was no statistically significant difference in pain scores between the cough and no cough group when analyzed for each demographic variable even when confounders were accounted for. The anxiety scores for both study groups before and after the procedure were similar and not significantly reduced. Conclusions: We observed a trend that cough reduced pain associated with the colposcopy-guided cervical biopsy but did not reach statistical significance. A similar outcome was observed in anxiety level, where anxiety was reduced in the cough group but was not statistically significant as compared with the no cough group. Further studies are necessary to assess various modalities in reducing pain and anxiety associated with colposcopy-guided cervical biopsy.